2016
DOI: 10.1093/isp/ekv004
|View full text |Cite
|
Sign up to set email alerts
|

Gas on the Fire: Great Power Alliances and Petrostate Aggression

Abstract: What causes petro-aggression? Conventional wisdom maintains that the regime type of petrostates has significant effects on a likelihood of petrostates launching revisionist MIDs While domestic politics is an important factor that explains the motivation and behavioral patterns of a petrostate, it says little about the international environment under which a petrostate decides to initiate conflicts. Petro-aggression does not take place devoid of concerns for the possible international backlash that its aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[58] A 2016 study argues that petrostates may be emboldened to act more aggressively due to the inability of allied great powers to punish the petrostate. [59] The great powers have strong incentives not to upset the relationship with its client petrostate ally for both strategic and economic reasons. [59] A 2017 study found evidence of the resource curse in the American frontier period of the Western United States in the 19th century (the Wild West).…”
Section: Other Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] A 2016 study argues that petrostates may be emboldened to act more aggressively due to the inability of allied great powers to punish the petrostate. [59] The great powers have strong incentives not to upset the relationship with its client petrostate ally for both strategic and economic reasons. [59] A 2017 study found evidence of the resource curse in the American frontier period of the Western United States in the 19th century (the Wild West).…”
Section: Other Effectsmentioning
confidence: 99%
“…[59] The great powers have strong incentives not to upset the relationship with its client petrostate ally for both strategic and economic reasons. [59] A 2017 study found evidence of the resource curse in the American frontier period of the Western United States in the 19th century (the Wild West). [60] The study found that "In places where mineral discoveries occurred before formal institutions were established, there were more homicides per capita historically and the effect has persisted to this day.…”
Section: Other Effectsmentioning
confidence: 99%